Effects of drying temperature and tempering duration on hybrid rice seed germination, thin-layer drying characteristics, and power requirement - Bawar, Rina A.; Foliente, Joanne P.; Yaptenco, Kevin F.; Cabiles, Mitchie Ann L. (2023)
This study presents the results of thin-layer drying tests for hybrid rice seeds. The independent factors were drying air temperature (45, 55, and 65 °C) and tempering duration (1, 2, and 4 h), while the dependent parameters were seed germination and drying characteristics, including drying rate, total and effective drying operation times, and power requirement. Considering one hybrid and 3 mo storage period after drying, the results showed that samples continuously dried at 45 and 55°C resulted in 91 and 86% germination percentages, respectively, which were above the acceptable Philippine national standard of at least 85%. However, when tempered for 2 or 4 h, even samples dried at 65°C resulted in more than 90% germination percentage. Tempered samples had an effective operation time of only 1 - 3 h, which was 50% less than those continuously dried (1.5 - 6 h of effective operation time). In effect, the total power used was halved by applying tempering. These results showed considerable advantages of tempering in terms of seed quality improvement and potential energy savings.
Keywords: Rice seeds -- Varieties; Seeds -- Analysis